Factores asociados a la salud mental de las personas que viven con VIH - Paiva Carvalho, Patrícia (2025)
The aim of this study was to investigate the risk and protective factors for the mental health of people living with HIV. A total of 237 participants were interviewed. Women predominated (51.5%), with an average age of 46.9 years, black and brown (67%), with low family income (65.4%) and low education level (62.8%). 72.6% of the interviewees were considered adherent to antiretroviral therapy and 33.3% presented emotional illness. The results showed that satisfaction with body image, social support, the resilience, the religiosity and the presence of morbidities had a positive impact on mental health, while the use of illicit drugs, being a woman and the stress experienced during the COVID-19 pandemic increased the chances of emotional illness.